PENYULUHAN SANITASI LINGKUNGAN DI KAMPUNG NELAYAN MACCINI BAJI KELURAHAN PUNDATA BAJI KABUPATEN PANGKAJENE KEPULAUAN - Manyullei, S.; Mustafa, I.; Bahtiar, L.O.; ,, Nurhikmah (Buletin Udayana Mengabdi, 2023)
Environmental sanitation is a formidable challenge for Maccini Baji Fisherman's Village, Pundata Baji Village, Pangkajene and Islands Regency because it is located on the coast with waterlogged conditions under the house. Community service was carried out in the form of environmental sanitation counseling with the aim of knowing the effect of environmental sanitation counseling on the knowledge of the community of Maccini Baji Fisherman Village, Pundata Baji Village, Pangkajene and Islands Regency in 2022. The method used, namely lectures and discussions with a one group pretest - posttest design using sheet media come back. The results of the data analysis showed that the average value of public knowledge before being given health counseling was 47.89 and after health counseling, the average value of community knowledge increased to 61.68. So that there is a difference in public knowledge before and after the extension. From the results of the Wilcoxon Signed Rank Test, the p-value is 0.003 < 0.05, then H o is rejected, which means that there is an effect of environmental sanitation counseling to the community in the Fisherman's Village, Pundata Baji Village, Pangkajene Regency. Islands in 2022. Therefore, improving environmental sanitation is very important to minimize the health impacts caused as an effort to improve the health status of the community. Keywords: Counseling, Sanitation, Environmental, Fisherman’s Village.